An unusual variant of atrophic dermatofibrosarcoma protuberans - Simone Silva da Costa Aragão; Everson José dos Santos Leite; Alberto Eduardo Cox Cardoso; Ricardo Luiz Simões Houly (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Dermatofibrosarcoma protuberans is an uncommon neoplasm that is most often seen in young adults. The most common clinical presentation is the protruding form; however, other subtypes are known, such as the atrophic. In 2012 there were only 33 reports of this variant in the literature. Many cases of Dermatofibrosarcoma protuberans in children are only discovered in adulthood because they were not diagnosed early. Due the high morbidity, we raise the need for attention from the dermatologist to recognize uncommon neoplasms in the clinical practice. We report a case of a 15-year-old patient diagnosed with atrophic Dermatofibrosarcoma protuberans on the back.